Mitos dan Pengetahuan Masyarakat Desa Tentang Kanker Payudara - Triratnawati, Atik; Novyantari, Dewi (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: Breast cancer is a scary disease among the society. Myths related to breast cancer that still exist in society will affect their preventive behavior.Objective: To identify the knowledge and mythsÂ  in society about breast cancer.Method: This ethnographic study used participatory observation and in-depth interviews with 12 informants consisting of 3 breast cancer patients and 9 non-breast cancer survivors in Jlegiwinangun Village, Kutowinangun, Kebumen, Central Java.Results and Discussion: Breast cancer was considered a frightening disease that can be caused by heredity, eating patterns, and unhealthy behavior. The existing of breast cancer myths, which dispread verbally is indicated that myths is important as preventive behavior.Conclusion: Knowledge and myths of breast cancer in Jlegiwinangun Village are a part of preventive behavior. The existing of Â myths are indicated the limited insight and information related aetiology, cure and prevention to breast cancer.Kata kunci: myths, community knowledge, village, breast cancer